UJI DAYA HAMBAT EKSTRAK DAUN SIRSAK (Annona muricata Linn) TERHADAP BAKTERI Escherichia coli SECARA IN VITRO - Luh Made Ionnandha; Musyarrafah; Sabariah; Ana Andriana (Nusantara Hasana Journal, 2023)
Soursop plant (Annona muricata Linn) is a type of traditional medicinal plant. Soursop plants are widely studied because the content of fruit and leaves can provide many benefits for society. Many people use parts of the soursop plant to cure various diseases such as diarrhea caused by Escherichia coli bacteria. Soursop leaf extract (Annona muricata Linn) is known to contain flavonoids, alkaloids, and saponins, tannins, acetogenins which can inhibit bacterial growth. The purpose of this study was to determine the inhibition of soursop leaf extract (Annona muricata Linn) towards against the growth of Escherichia coli bacteria. This research was conducted in the Research laboratory of the Faculty of Medicine of Al-Azhar Islamic University using the method of extrasion (maceration) with ethanol solvent. The design used in this study was a Complete Randomized Design (RAL) with 4 treatment groups and 2 controls (positive ciprofloxacin and negative aqudest). The sample data obtained was then analyzed using SPSS version 23. The results of this study obtained the diameter of the inhibitory zone in 4 treatment groups. The largest inhibitory zone dimater is 10,25 mm at a concentration of 100%, and the lowest inhibitory power is 2 mm at a concentrationof 25%. Based on the results of the analysis carried out, a significant difference was obtained between the treatment groups with a value (p<0.05). Soursop leaf extract (Annona muricata Linn) has an inhibitory power against the growth of Escherichia coli bacteria.